PROGRAM DIGITAL MARKETING SEBAGAI MEDIA PROMOSI UMK SWASTIKA KARYA ABADI - Yanti, Dewi; Octariadi, Barry Ceasar (Jurnal Abdi Insani, 2024)
The Swastika Karya Abadi Micro Business Unit (UMK), focusing on basic food trade in West Kalimantan, has been running for 5 years with conventional marketing. However, the product marketing method used by partners is still relatively passive because they only wait for buyers to come to the sales location. This article details community service activities carried out to improve understanding and skills in marketing products through digital media. The service activities carried out target the UMK Swastika's basic understanding of product marketing and introducing promotional strategies through digital media, as well as increasing partners' insight in carrying out graphic designs for products. The training was carried out by providing the team, preparing the place and tools, socializing the material and evaluating using pre-test and post-test questionnaires. The material provided in the training is online marketing strategies using Facebook social media and the use of the Adobe Photoshop graphics application. Service activities proceed with successful planning and preparation stages with team members who understand their duties. The training carried out is also effective in increasing partners' understanding of digital marketing strategies. This can be seen from the results of the pre-test and post-test surveys carried out which show that partners are starting to be confident in designing graphic designs for their own products. Apart from that, socialization of online marketing strategies is also going well because partners have also succeeded in using paid advertising on Facebook to market their products. In other words, this service activity succeeded in increasing the understanding and digital marketing skills of UMK Swastika to support their business growth.